A large‐scale measurement of dielectric properties of normal and malignant colorectal tissues obtained from cancer surgeries at Larmor frequencies. Issue 11 (14th October 2016) - Li, Zhou; Deng, Guanhua; Li, Zhe; Xin, Sherman Xuegang; Duan, Song; Lan, Maoying; Zhang, Sa; Gao, Yixin; He, Jun; Zhang, Songtao; Tang, Hongming; Wang, Weiwei; et al.
Abstract : Purpose: Knowledge of dielectric properties of malignant human tissues is necessary for the recently developed magnetic resonance (MR) technique called MR electrical property tomography. This technique may be used in early tumor detection based on the obvious differentiation of the dielectric properties between normal and malignant tissues. However, the dielectric properties of malignant human tissues in the scale of the Larmor frequencies are not completely available in the literature. In this study, the authors focused only on the dielectric properties of colorectal tumor tissue. Methods: The dielectric properties of 504 colorectal malignant samples excised from 85 patients in the scale of the Larmor frequencies were measured using the precision open‐ended coaxial probe method. The obtained complex‐permittivity data were fitted to the single‐pole Cole–Cole model. Results: The median permittivity and conductivity for the malignant tissue sample were 79.3 and 0.881 S/m at 128 MHz, which were 14.6% and 17.0% higher, respectively, than those of normal tissue samples. Significant differences between normal and malignant tissues were found for the dielectric properties ( p < 0.05). Conclusions: Experimental results indicated that the dielectric properties were significantly different between normal and malignant tissues for colorectal tissue. This large‐scale clinical measurement provides more subtle base data to validate the technique of MR electrical property tomography.